METHOD AND SYSTEM FOR DELIVERING BIOMECHANICAL FEEDBACK TO HUMAN AND OBJECT MOTION - FORTENBAUGH, Dave; HANSEN, Ben; NOLAN, Joe; ROBINSON, Keith (2020)
A method and system to deliver biomechanical feedback utilizes three major elements: (1) multiple hardware data capture devices, including optical motion capture, inertial measurement units, infrared scanning devices, and two-dimensional RGB consecutive image capture devices, (2) a cross-platform compatible physics engine compatible with optical motion capture, inertial measurement units, infrared scanning devices, and two-dimensional RGB consecutive image capture devices, and (3) interactive platforms and user-interfaces to deliver real-time feedback to motions of human subjects and any objects in their possession and proximity.